2015
DOI: 10.1007/s00296-015-3211-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between comorbidities and pain, physical function and quality of life following hip and knee arthroplasty

Abstract: The aim of the study was to examine the relationship between comorbidities and pain, physical function and health-related quality of life (HRQoL) after total hip arthroplasty (THA) and total knee arthroplasty (TKA). A cross-sectional retrospective survey was conducted including 19 specific comorbidities, administered in patients who underwent THA or TKA in the previous 7–22 months in one of 4 hospitals. Outcome measures included pain, physical functioning, and HRQoL. Of the 521 patients (281 THA and 240 TKA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 32 publications
6
71
1
2
Order By: Relevance
“…These findings are consistent with prior evidence, which demonstrates that poorer baseline mental and emotional health is associated with smaller improvement in function after TKA [4,5,13,16,17,19,24,26,27,40,43,44]. By comparison, patient comorbidities and age have little effect on PROM scores after TKA [13,32].…”
Section: Discussionsupporting
confidence: 81%
“…These findings are consistent with prior evidence, which demonstrates that poorer baseline mental and emotional health is associated with smaller improvement in function after TKA [4,5,13,16,17,19,24,26,27,40,43,44]. By comparison, patient comorbidities and age have little effect on PROM scores after TKA [13,32].…”
Section: Discussionsupporting
confidence: 81%
“…Second, there were limited data overall, and particularly in respect to the impact of comorbidities on physical activity. Peter et al 41 highlighted the prevalence of major comorbidities such as musculoskeletal pain, hypertension and cancer, which can all impact on exercise and physical activity participation. Further research to explore the potential importance of this as a barrier is therefore warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that statin users are usually diagnosed with dyslipidemia, they are likely to have a higher ASA classification or Charlson comorbidity index score than non-statin users are. A previous study reported that pain after joint arthroplasty was associated with preoperative comorbidities of patients 26. Therefore, we performed PS matching to balance the covariates regarding preoperative comorbidities (ASA classification, Charlson comorbidity index, anemia (hemoglobin ≤10 mg/dL), nutrition status (body mass index and serum albumin, mg/dL), and kidney function (estimated glomerular filtration rate: ≥90 mL/min 1.73/m 2 )).…”
Section: Discussionmentioning
confidence: 99%